BRAZILIAN JOURNAL OF SPORTS MEDICINE: 10 YEARS OF INDEXATION ON THE WEB OF SCIENCE REVISTA BRASILEIRA DE MEDICINA DO ESPORTE: 10 ANOS DE INDEXAÇÃO NA WEB OF SCIENCE REVISTA BRASILEÑA DE MEDICINA DEL DEPORTE: 10 AÑOS DE INDEXACIÓN EN LA WEB OF SCIENCE - Coimbra D.R.* (2023)
© 2023, Redprint Editora Ltda. All rights reserved.Analyses of scientific production have attracted the interest of researchers, as they help to control the quality of what is published, identify relevant themes, and, thus enable scientific advances. Therefore, the objective of this study was to analyze the scientific production of the Brazilian Journal of Sports Medicine on the Web of Science database through a bibliometric analysis. The data were analyzed in relation to the publications, the authors, and the RBME. During the period of indexation on the Web of Science, which corresponds to the last decade, the RBME published 896 documents, most of which were original articles (801, 89.3%). The most cited keywords were exercise (117 studies), resistance training (37), and physical activity (34). Brazilian institutions had the highest number of publications, followed by Portugal and Spain, and there were also articles published in the USA, Canada, and the United Kingdom. USP and UNESP were the institutions with the greatest number of publications in the RBME over the last decade. Ten different collaboration clusters were identified, with researcher Edilson Serpeloni Cyrino standing out with the largest collaboration network. The ten years of indexation on the Web of Science reveal the consolidation of the RBME on the international scene, which has resulted in increasing views of and citations from the studies published, as well as attracting researchers from institutions of other countries to publish their work. Level of evidence II; Review.